2004
DOI: 10.1002/j.1556-6978.2004.tb01840.x
|View full text |Cite
|
Sign up to set email alerts
|

On Becoming Allies: A Qualitative Study of Lesbian‐, Gay‐, and Bisexual‐Affirmative Counselor Training

Abstract: The authors present a qualitative analysis of a process by which a research team of counselors-in-training confronted their heterosexist biases while investigating heterosexual attitudes toward sexual minorities. Members of the research team discovered that it was essential to reflect on and evaluate their attitudes. assumptions. and biases before they could conduct scientific research about affirmative attitudes toward lesbian. gay male. and bisexual male and female individuals. Self-reflective narratives wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 23 publications
6
52
0
1
Order By: Relevance
“…Several of the participants reported that they knew other heterosexuals whose fears became a barrier to activism. Dillon et al (2004) also found this theme among their sample of heterosexual LGB-affirmative counselors and labeled it homophobic self-consciousness. This fear of being gay by association may constitute a significant barrier that prevents heterosexuals from connecting and building social-justice alliances with sexual minorities.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Several of the participants reported that they knew other heterosexuals whose fears became a barrier to activism. Dillon et al (2004) also found this theme among their sample of heterosexual LGB-affirmative counselors and labeled it homophobic self-consciousness. This fear of being gay by association may constitute a significant barrier that prevents heterosexuals from connecting and building social-justice alliances with sexual minorities.…”
Section: Discussionmentioning
confidence: 91%
“…Another study (Dillon et al 2004) used consensual qualitative research methodology (CQR; Hill et al 1997) to examine the development of ten heterosexual counselor allies. These ten counselors-in-training volunteered to participate in a yearlong research team focused on understanding heterosexual attitudes toward sexual minorities.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research indicated that LGBT clients who engaged in counseling often report being dissatisfied with the experience (Grove, 2009;O'Neill, 2002). Furthermore, the literature showed that both counselors in-training and counselors in the field reported a lack of dedication to affirmative practice and training from their counselor education programs and an overall lack of competence regarding working with LGBT clients (Dillon, Worthington, Savoy, Rooney, Becker-Schutte, & Guerra, 2004;Farmer, 2011;Matthews, 2005).…”
Section: Implications For Counselor Education Studentsmentioning
confidence: 99%